Al-Azhar Reform and the Pressures of Globalization: Reorienting Turath Pedagogy in the Twenty-First Century - El-Masry, Rifaat Hamdi (Bestari, 2025)
This article examines ongoing reform efforts within al-Azhar University as it responds to the multidimensional pressures of globalization and the demands for modernizing Islamic scholarship. Through institutional analysis and interviews with Azharite scholars, the study explores how traditional turath-based pedagogy—characterized by classical texts, memorization, and sanad transmission—is being reinterpreted to address contemporary social, scientific, and ethical issues. The findings indicate that reform initiatives aim to strengthen critical thinking, integrate modern humanities and social sciences, and enhance global engagement, while preserving the authenticity of classical Islamic knowledge. However, tensions remain between traditionalists who fear epistemic dilution and reformists advocating interdisciplinary approaches. The article argues that sustainable reform requires balancing epistemological continuity with adaptive educational strategies that prepare graduates to contribute to global intellectual discourse. This study offers insight into how one of the world’s oldest Islamic institutions negotiates the relationship between heritage and modernity.